Determinant of Economic Growth in ASEAN Countries (Indonesia, Thailand, Malaysia, Singapura, Philipines) 2010-2019 - Lilies Setiartiti; Fitri Rahmadani (Journal of Economics Research and Social Sciences, 2023)
This research aims to analyze the effect of Foreign Direct Investment, Labor Force, External Debt, and Economic Freedom, on the Economic growth of Selected ASEAN Countries. The data used in this study is annual data for the period 2010-2019 sourced from The World Bank, Ceic Data, and Heritage.org. The analytical method used in this research is panel data analysis supported by Eviews 11.0. The results is show that foreign investment has a positive and insignificant effect on economic growth the workforce has a significant and positive effect on economic growth, foreign debt has a positive and dignified effect, and economic freedom has a significant and positive effect on economic growth.